VAN ROOYEN, J.M. Inventory of documents - VAN ROOYEN, J.M. (ARCA, 2018)
Private papers of J.M. van Rooyen, National Party Candidate for Senator in 1948.
COVERAGE 1948-1949; 1 File; 0,11 Metre.
Keywords: VAN ROOYEN, J.M.; Inventories; Politicians; National Party